(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The article concerns the motivation and attitude of students and the effects of Polish as a foreign language courses conducted for refugees from Ukraine at the University of Szczecin after February 24, 2022. The results of the survey conducted on a group of 257 respondents indicate that students have a strong and diverse motivation to learn Polish. Students treated the courses as an essential element of learning. Still, at the same time, over 75% of participants indicated that the way to master the language effectively is to use Polish in every situation. Nearly half considered it essential to master the grammar of the Polish language. Students indicated the most difficult elements of learning Polish: writing, pronunciation of specific words and speaking in general. The skills requiring only passive language knowledge caused minor problems. The results indicate that organizing Polish language courses for refugees is extremely necessary. Students learn the language and gain confidence in using it in everyday situations.